Joint Link Scheduling, Beamforming and Power Control for Maximizing the Sum-Rate of Cognitive Wireless Mesh Networks - Islam, M. H.; Dziong, Z. (2011 IEEE 73rd Vehicular Technology Conference (VTC Spring), 2011)
We consider a time division multiple access (TDMA) based cognitive wireless mesh network (CWMN), where pairs of mesh nodes communicate with each other by sharing a spectrum that is licensed to a primary network with multiple primary users (PUs) who have exclusive right to occupy the spectrum. All the mesh nodes are equipped with multiple antennas capable of beamforming. For such a system, we investigate joint link scheduling, beamforming and power control with the objective of maximizing the sum-rate of CWMN under the minimum data rate requirement constraint of each mesh link (mesh node pair), total transmit power constraint of CWMN in a time slot, and maximum allowable interference constraint of each primary user (PU). The sum-rate maximization subject to the above mentioned constraints gives rise to a non-convex mixed integer nonlinear programming (MINLP) problem which is practically intractable. In order to find an efficient solution of the MINLP, we employ an extended duality based algorithm that uses multiple penalty multipliers to remove the duality gap of the non-convex MINLP problem. Simulation results show that the extended duality based solution performs very close to the optimal solution obtained by exhaustive search algorithm.